2018
DOI: 10.5056/jnm17147
|View full text |Cite
|
Sign up to set email alerts
|

Esophagography in Patients With Esophageal Achalasia Diagnosed With High-resolution Esophageal Manometry

Abstract: Background/AimsHigh-resolution esophageal manometry (HREM) is considered to be the gold standard for the diagnosis of achalasia. However, the Japan Esophageal Society recommends that esophagography is also accurate in either diagnosing or excluding the disorder. Accordingly, we compared the efficacy of esophagography and HREM in diagnosing achalasia patients with upper gastrointestinal symptoms.MethodsHREM was performed in 126 patients with dysphagia. The final diagnosis of achalasia was done using HREM. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Additionally, the gastric tube is placed in the chest and may be in a state of passive expansion[ 7 ]. In the present case, we found that the patient had gastric tube mild dilatation before surgery (Figure 1C )[ 8 ]. These factors lead to delayed gastric emptying and an increase in the incidence of gastroesophageal reflux[ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the gastric tube is placed in the chest and may be in a state of passive expansion[ 7 ]. In the present case, we found that the patient had gastric tube mild dilatation before surgery (Figure 1C )[ 8 ]. These factors lead to delayed gastric emptying and an increase in the incidence of gastroesophageal reflux[ 7 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 76%
“…However, as the positive predictive accuracy was 96%, the authors concluded that the barium oesophagram is a useful tool in achalasia diagnosis 11 . Similar sensitivity and specificity rates were obtained in another study comparing barium swallow studies with HRM; the diagnostic sensitivity, specificity and accuracy of the barium oesophagram were 78.3%, 88.0% and 83.0%, respectively 14 . Consequently, it may be concluded that diagnosing achalasia by using barium oesophagram alone has a limited yield.…”
Section: Achalasia Diagnosismentioning
confidence: 72%
“…11 Similar sensitivity and specificity rates were obtained in another study comparing barium swallow studies with HRM; the diagnostic sensitivity, specificity and accuracy of the barium oesophagram were 78.3%, 88.0% and 83.0%, respectively. 14 Consequently, it may be concluded that diagnosing achalasia by using barium oesophagram alone has a limited yield. The technique of timed barium oesophagram (TBO) is similar to the usual barium swallow study but uses set time intervals (one, two and five minutes) after ingestion of a fixed barium suspension to measure the height and width of the barium column in order to assess oesophageal emptying more objectively (Figure 1).…”
Section: Recommendation 12mentioning
confidence: 99%
“…Another study which only recruited patients with achalasia reported that the sensitivity of barium esophagography in the diagnosis of achalasia was 78.3%, which was still not enough. 6 We have thought of the possible usefulness of a solid meal, specifically the Onigiri. Recently, a number of studies have been carried out to examine the usefulness of HRM using solid meals rather than a liquid medium, and the Onigiri has been shown to be one of the best candidate solid mediums.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the conventionally-performed barium esophagography is useful for detecting EMDs by evaluating the extent of esophageal obstruction in relation to fluids. 5 , 6 However, all the EMDs other than the most severe EMD, namely achalasia does not usually cause stagnation of liquid barium. The sensitivity and specificity of esophagography using liquid barium in screening for EMDs were not sufficient.…”
Section: Introductionmentioning
confidence: 99%